Nb-containing hematites Fe2-xNbxO3: The role of Nb5+ on the reactivity in presence of the H2O2 or ultraviolet light - Silva, Adilson C.; Oliveira, Diana Q. L.; Oliveira, Luiz C. A.; Anastacio, Alexandre S.; Ramalho, Teodorico C.; Lopes, Joao H.; Carvalho, Hudson W. P. [UNESP]; Torres, Claudia E. Rodriguez (Elsevier B.V., 2009)
A series of Nb-containing hematites, Fe-2-xNbxO3 (%Nb = 0.00, 1.49, 5.00 and 9.24) was prepared using the conventional co-precipitation method. Mossbauer and temperature-programmed reduction (TPR) measurements suggested the formation of the crystalline phase with partial substitution of Fe3+ by Nb5+ in the structure. N-2 adsorption/desorption revealed that the presence of Nb has a remarkable effect on the textural properties of the material with an increase in the BET surface area. The reactivity of Fe2-xNbxO3 was investigated using the oxidation of the methylene blue dye used as a model pollutant. The obtained results showed that the presence of Nb seems not to act directly promoting the H2O2 decomposition, but improving the dye oxidation. The analysis using the ESI-MS technique showed partial oxidation observed through different intermediates before the mineralization. This suggests the use of Nb-doped hematite as an efficient catalyst in degradation reactions in the presence of H2O2 or ultraviolet light. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Hematite; Niobium; Organic oxidation; ESI-MS